PENGARUH KEBIJAKAN DIVIDEN, PERTUMBUHAN PERUSAHAAN DAN STRUKTUR AKTIVA TERHADAP PROFITABILITAS PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI TAHUN 2019-2022 DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Rosadi, Gufron; Wahyuni, Ika; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Financial management aims to manage the finances of a company in order to maximise its efficiency and effectiveness, whether it is a company, financial institution, government agency, or individual. A company is a location where manufacturing or operations involving the creation of goods or services take place. The purpose of this study was to determine the effect of Dividend Policy, Company Growth and Asset Structure on Profitability in LQ-45 Companies Listed on the IDX in 2019-2022 with Capital Structure as an Intervening Variable. The reason the researchers took the object was because there was a phenomenon on the weekend of August 2022 there were 39 that had released their financial statements. Overall, the net profit of 39 LQ-45 companies increased 78.4% year-on-year to IDR 188 trillion. The population of this study consists of LQ-45 Index companies with a total of 45 companies in it and listed on the Indonesia Stock Exchange between 2019 and 2022. The sampling strategy in this study combines purposive sampling with non-probability sampling. Data analysis and hypothesis testing using structural equation modelling (PLS-SEM). The results of direct effect hypothesis testing using smart PLS 3. 0, shows that Dividend Policy has a negative but significant effect on Capital Structure thus H1 is accepted; Sales Growth has a positive but insignificant effect on Capital Structure thus H2 is rejected; Asset Structure has a negative but significant effect on Capital Structure thus H3 is accepted; Dividend Policy has a negative but significant effect on Profitability thus H4 is accepted; Company Growth has a positive but insignificant effect on Profitability thus H5 is rejected; Asset Structure has a negative but significant effect on Profitability thus H6 is accepted; Capital Structure has a negative but significant effect on Profitability thus H7 is accepted; Dividend Policy has a significant positive effect on Profitability through Capital Structure thus H8 is accepted; Company Growth has a negative but insignificant effect on Profitability through Capital Structure thus H9 is rejected; Asset Structure has a significant positive effect on Profitability through Capital Structure thus H10 is accepted.